Analisis Dampak Masjid Terhadap Kesejahteraan Masyarakat - Amelia Anggeraini; Ulil Albab; Heri Sutopo; Mawardi (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study focuses on analyzing the social and economic impact of the Thoriqul Khoir mosque in Tanjung Karang Barat district on the welfare of the local community during the period May, June and July 2024. This mosque was chosen because it is the oldest mosque in the region and has a strategic location that is easily accessible, so it becomes the center of religious and social activities of the community. The approach used in this study is qualitative with descriptive methods. Data collection was conducted through in-depth interviews with mosque administrators, pilgrims, local communities, and small businesses in the mosque area. In addition, direct observation is also applied to observe the activities in the mosque and the interaction of the surrounding community. The results showed that the Thoriqul Khoir mosque has a significant positive impact on the economic and social aspects of the community. In terms of economy, this mosque is a center for the development of various MSMEs owned by the surrounding community. Pilgrims who come every day provide opportunities for residents to open businesses such as food stalls and shops for worship supplies, which has an impact on increasing residents ' income. In terms of social, the mosque is not only a place of worship, but also as a center of education and community empowerment activities. Regular recitation and study programs involving many participants, including 200 santriwan and santriwati, strengthened the religious education and spirituality of the community. In addition, social activities and celebrations of Islamic holidays organized by the mosque also play an important role in building social solidarity among the community, by involving volunteers and active support from the surrounding community. Overall, this study confirms that the Thoriqul Khoir Mosque not only serves as a place of worship, but also as a major catalyst for the economic and social well-being of the surrounding community